Frozen 3D printing stent with synergistic signal molecules as well as preparation method and application of frozen 3D printing stent
By using frozen 3D printed ink compositions and electrospinning technology using synergistic signaling molecules, the problems of poor mechanical properties of bone tissue engineering scaffolds and difficulty in regulating phenotype transformation of macrophages are solved, and the structural integrity, vascularization and immunomodulatory functions of bone repair scaffolds are improved.
Patent Information
- Application Number
- CN202411603188.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing bone tissue engineering scaffolds have problems such as poor mechanical properties, discomfort in degradation speed, poor biological function and prone to inflammatory responses, and it is difficult to effectively regulate the M1/M2 phenotype transformation of macrophages.
Using a frozen 3D printed ink composition with synergistic signal molecules, including a first porous carrier loaded with CO molecular prodrug and a second porous carrier loaded with NO molecular prodrug, the scaffold is printed layer by layer by layer by layer by frozen 3D printing technology, and a nano-staple fiber dispersion solution is prepared using electrospinning technology during the printing process, enhancing the biocompatibility and vascularization ability of the scaffold.
A relatively complete bone repair scaffold was achieved, which promoted vascularization and stabilized bone formation, regulated the M1/M2 balance of macrophages, and enhanced immune surveillance and immune regulation functions.
Smart Images

Figure CN119564926A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of bone tissue engineering, and in particular relates to a frozen 3D printed scaffold with synergistic signal molecules, and a preparation method and application thereof. Background Art
[0002] Bone tissue engineering technology is the key to repairing the structure and function of bone defects. The ultimate goal of bone tissue engineering technology is to reconstruct the functional structure of the bone defect site and achieve the bionics of the structure and mechanical properties of bone tissue engineering scaffolds with normal bone tissue. Soft tissue and hard tissue injuries usually occur simultaneously in severe bone defects, cartilage damage, tooth loss or tendon damage, and currently only single soft tissue or hard tissue repair is far from enough.
[0003] The selection of appropriate scaffold materials is one of the key factors for the success of bone repair. Currently, the main treatment methods for bone defects in clinical practice are the use of autologous bone transplantation or allogeneic bone transplantation. Autologous bone is a nearly ideal material due to its biological tolerance, strength, elasticity and good forming ability; however, the amount of autologous bone is limited, and the removal site may cause pain or discomfort, leading to complications. Allogeneic bone transplantation is an alternative to autologous bone transplantation, but allogeneic bone transplantation has the risk of transmitting donor diseases and causing infection, and may also cause immune rejection in the recipient organism.
[0004] At present, the main problems of bone tissue engineering scaffolds include poor mechanical properties, too fast or too slow degradation, poor biological functionality, and easy to cause inflammatory reactions. Therefore, in response to these problems, the research on using tissue engineering to construct composite materials that simulate the structure of human bone tissue has received more and more attention. Ideal bone repair materials can not only simulate the tissue microenvironment, but also regulate the activity of multiple cells to achieve ideal biological functions. Designing bone repair scaffolds that imitate the natural layered structure of natural bones for the repair of soft tissue and hard tissue will help improve the life compatibility of bone scaffolds and their ability to induce osteogenic differentiation of stem cells in vitro.
[0005] Bone immunomodulation is a new strategy in recent years to promote bone immune balance by regulating the interaction between immune cells and bone cells. It involves the interaction between bone regeneration and immune system function. After the implantation of scaffolds with good immunomodulatory properties, the immune system is activated, the body releases bioactive molecules, regulates local inflammatory responses, and promotes the differentiation of bone marrow stem cells into osteoblasts, thereby promoting bone growth and repair. Bone repair is a precisely regulated process involving multiple steps such as inflammatory response, angiogenesis, bone resorption and new bone formation. Macrophages are one of the most important effector cells in the body's immune response and play a dynamic regulatory role in balancing osteoclasts and osteogenesis.
[0006] The key to the balance between osteoclastogenesis and osteoblastogenesis in bone repair by macrophages lies in the transformation of their phenotype and the difference in the cytokines released. Macrophages can transform into different phenotypes according to different physiological needs, such as classically activated M1 macrophages and selectively activated M2 macrophages. M1 macrophages are mainly involved in inflammatory response and osteoclastogenesis, and activate and recruit other immune cells by producing proinflammatory cytokines, as well as destroying old bones to remove dead bone and debris at the site of injury; while M2 macrophages promote tissue repair and osteogenesis by producing anti-inflammatory cytokines to reduce inflammation, thereby promoting new bone formation. In the early stage of bone repair, an appropriate inflammatory response is necessary to remove dead cells and debris at the site of injury. However, as bone repair proceeds, macrophages need to transform from M1 to M2 to promote the formation and repair of bone tissue. Therefore, regulating the M1 / M2 balance of macrophages is crucial for regulating osteoclastogenesis and osteoblastic activity.
[0007] Regulating the M1 / M2 phenotype conversion of macrophages is crucial for bone repair. In the early stage of scaffold implantation, it is hoped that the expression of inflammatory genes can be upregulated to promote the conversion of macrophages to the M1 phenotype, so as to achieve the purpose of clearing inflammation at the site of bone damage. If the M1 phenotype is maintained continuously, newly generated bone cells may be killed later. Therefore, how to regulate the phenotype of macrophages has become an urgent problem to be solved.
[0008] Due to the complexity and diversity of the shape and structure of bone defects, current research is increasingly using 3D printing technology to construct bone graft substitutes. 3D printing, commonly known as additive manufacturing, refers to designing a 3D model through computer-aided design (CAD) software and printing it layer by layer. Each layer can accurately control the position and thickness of the material, which helps to manufacture high-quality scaffolds. 3D printing can achieve personalized customization and customize the scaffold to fit the bone defect site according to the patient's needs. This technology also helps to accurately control the microstructure of the scaffold, including pore size, total pore volume and shape. Although there is currently a lack of clinical evidence and regulatory approval, 3D printing technology can meet the personalized needs of patients and print three-dimensional scaffolds with controllable structure and pore size to promote cell migration and bone growth.
[0009] Currently, due to the characteristics of the printing technology itself, the scaffolds obtained by traditional extrusion 3D printing may form pores in the material, and the processing accuracy is difficult to control, which affects the porosity, pore size, connectivity, etc. of the scaffold. During the printing process, it is difficult to process and shape the slurry with good fluidity. The printed scaffolds are prone to structural collapse and side hole collapse, which affects the integrity and functionality of the bone scaffold structure.
[0010] Compared with traditional extrusion 3D printing, cryo-3D printing can control the fluidity of materials through low temperature, overcoming the problems of easy collapse and deformation during the general extrusion 3D printing process, and achieving more precise control of shape and structure. However, existing cryo-3D printing also makes it difficult to obtain bone repair scaffold materials with better performance. Summary of the invention
[0011] In order to improve the deficiencies of the prior art, the present invention provides a frozen 3D printed scaffold with synergistic signal molecules and a preparation method and application thereof, which can obtain a scaffold with a relatively complete structure, timely vascularization and stable bone formation.
[0012] The present invention provides the following technical solutions:
[0013] In a first aspect, the present invention provides an ink composition having a synergistic signal molecule, the ink composition comprising a first porous carrier loaded with a CO molecular prodrug and a second porous carrier loaded with a NO molecular prodrug, the surface of the first porous carrier being coated with a first encapsulation layer, the first encapsulation layer being used to seal the CO molecular prodrug in the pores of the first porous carrier, and the first encapsulation layer being capable of self-degrading and releasing CO molecules under high oxygen activity conditions; the surface of the second porous carrier being coated with a second encapsulation layer, the second encapsulation layer being used to seal the NO molecular prodrug in the pores of the second porous carrier, and the second encapsulation layer being capable of self-degrading and releasing NO molecules under acidic conditions.
[0014] According to an embodiment of the present invention, the ink composition further comprises hydroxyapatite, bioactive glass, polylactic acid, polyvinyl alcohol and chitosan.
[0015] According to an embodiment of the present invention, the ink composition further comprises a solvent, and the solvent comprises one or more of deionized water, ethanol, propanol, dichloromethane, dimethyl sulfoxide, dimethylformamide, and glycerol.
[0016] According to an embodiment of the present invention, the CO molecular prodrug is selected from a material that can release CO molecules in body fluids, preferably selected from one or more of metal carbonyl compounds such as carbonyl manganese, carbonyl imidazoles, nitroxyl compounds (such as silver nitrate, nitroxyl iron, etc.), heme derivatives (such as thiohemoglobin, etc.), and CO metal complexes, such as carbonyl manganese.
[0017] According to an embodiment of the present invention, the NO molecular prodrug is selected from materials that can release NO molecules in body fluids, preferably selected from one or more of arginine, citrulline, dimethylarginine, nitro drugs (such as sodium nitroprusside, nitrobenzene, etc.), organic nitrates (such as glyceryl trinitrate, isosorbide mononitrate, etc.), nitrosothiol compounds, metal-nitrosyl complexes, and diazeniumdiolate salts, such as arginine.
[0018] According to an embodiment of the present invention, the first porous carrier is selected from biocompatible mesoporous materials, preferably selected from one or more of mesoporous hydroxyapatite, mesoporous bioactive glass, mesoporous silicon, mesoporous carbon, metal organic frameworks (MOFs, such as ZIF series), metal oxide mesoporous materials (such as mesoporous titanium dioxide, mesoporous ferrosoferric oxide, etc.), for example, mesoporous hydroxyapatite.
[0019] According to an embodiment of the present invention, the second porous carrier is selected from biocompatible mesoporous materials, preferably selected from one or more of mesoporous bioactive glass, mesoporous hydroxyapatite, mesoporous silicon, mesoporous carbon, metal organic frameworks (MOFs, such as ZIF series), metal oxide mesoporous materials (such as mesoporous titanium dioxide, mesoporous ferrosoferric oxide, etc.), for example, mesoporous bioactive glass.
[0020] According to an embodiment of the present invention, the first encapsulating layer is selected from one or more of chitosan, polylactic acid, polyvinyl alcohol, tannic acid, sodium alginate, and gelatin, for example, chitosan.
[0021] According to an embodiment of the present invention, the second encapsulating layer is selected from one or more of tannic acid, chitosan, polylactic acid, polyvinyl alcohol, sodium alginate, and gelatin, for example, tannic acid.
[0022] According to an embodiment of the present invention, the mass ratio of the first porous carrier loaded with CO molecular prodrug to the second porous carrier loaded with NO molecular prodrug is 1 (1-5):1 (1-5), for example, 5:1.
[0023] In a second aspect, the present invention further provides a method for freezing 3D hierarchical printing of a stent using the above ink composition, comprising the following steps:
[0024] (1) mixing polylactic acid and hydroxyapatite powder to print a base support;
[0025] (2) mixing the first porous carrier loaded with CO molecular prodrug, hydroxyapatite, bioactive glass powder, polyvinyl alcohol and chitosan solution for cryo-3D printing to obtain a drug-loaded stent;
[0026] (3) Fixing the base support and the drug-loaded support to obtain a first composite support.
[0027] According to an embodiment of the present invention, step (3) includes the following steps: immersing the base support in an organic solvent so that the base support is completely covered with the organic solvent, dissolving the polylactic acid on the surface of the base support, contacting and bonding the base support with the drug-loaded support, and drying to obtain a first composite support.
[0028] As an example, step (3) includes the following steps: compounding the drug-loaded stent and the base stent by means of an organic solvent, dichloromethane, immersing the base stent in dichloromethane so that its surface is evenly covered with a layer of dichloromethane, taking it out and placing it on the drug-loaded stent to ensure that the two are in contact and bonded together, and placing it in a ventilated environment to dry. As the solvent dichloromethane evaporates, PLA will re-solidify to form a solid bonding layer, so that the base stent and the drug-loaded stent are firmly compounded together to obtain a first composite stent.
[0029] According to an embodiment of the present invention, after step (2) and before step (3), the following step is further included: immersing the drug-loaded stent in a sodium alginate solution and drying it.
[0030] According to an embodiment of the present invention, the concentration of sodium alginate is 5-60 g / L, preferably the concentration of sodium alginate is 10-60 g / L, for example, 10 g / L, 20 g / L, 30 g / L, 40 g / L.
[0031] According to an embodiment of the present invention, the drying is freeze drying, and the freeze drying temperature is -30°C to -10°C, and the time is 15 to 35 hours, for example, the freeze drying temperature is -20°C, and the time is 24 hours.
[0032] According to an embodiment of the present invention, step (3) further includes step (4): dissolving the second porous carrier loaded with NO molecular prodrug in a solvent and performing electrospinning to obtain a fiber membrane, dispersing the fiber membrane in a dispersion liquid and homogenizing at high speed to obtain a nano-short fiber dispersion solution, immersing the first composite scaffold in the nano-short fiber dispersion solution, and then drying to obtain a second composite scaffold.
[0033] According to an embodiment of the present invention, the drying is freeze drying, for example freeze drying at -20°C.
[0034] According to an embodiment of the present invention, step (4) comprises the following steps: forming a suspension of mesoporous bioactive glass + arginine / tannic acid powder in anhydrous ethanol, preparing a bioactive glass + arginine / tannic acid fiber membrane by electrospinning, dispersing the fiber membrane in tert-butanol solvent and homogenizing at high speed to obtain a nano-short fiber dispersion solution, immersing the first composite scaffold in the nano-short fiber dispersion solution, and freeze-drying at -20°C to obtain a second composite scaffold.
[0035] According to an embodiment of the present invention, in the suspension of step (4), the concentration of arginine is 10-50 μg / mL, for example, 25 μg / mL.
[0036] According to an embodiment of the present invention, the conditions for electrospinning in step (4) are: using an electrospinning machine at a voltage of 17 kV, a flow rate of 1 mL / h, and a working distance of 20 cm to electrospin to obtain a fiber membrane.
[0037] According to an embodiment of the present invention, in step (1), the mass ratio of polylactic acid to hydroxyapatite is 1:(1)3, for example, 4:6.
[0038] According to an embodiment of the present invention, the step (2) comprises the following steps:
[0039] a) loading the CO molecular prodrug into the first carrier, and coating the CO molecular prodrug-first carrier with a first encapsulating material to form a first porous carrier loaded with the CO molecular prodrug;
[0040] b) loading the NO molecular prodrug into the second carrier, and coating the NO molecular prodrug-second carrier with a second encapsulating material to form a second porous carrier loaded with the NO molecular prodrug;
[0041] c) mixing a polyvinyl alcohol solution, a chitosan solution, a first porous carrier loaded with a CO molecular prodrug, a second porous carrier loaded with a NO molecular prodrug, hydroxyapatite powder, and a bioactive glass powder to prepare a printing ink, and printing the ink layer by layer using a cryo-3D printing technique to obtain a drug-loaded stent.
[0042] According to an embodiment of the present invention, in step a), the molar ratio of the CO molecular prodrug to the first carrier is 1:(1-2), for example, the molar ratio of the mesoporous hydroxyapatite to carbonyl manganese is 1:1.
[0043] According to an embodiment of the present invention, loading carbonyl manganese powder into mesoporous hydroxyapatite comprises the following steps: adding carbonyl manganese powder and mesoporous hydroxyapatite into PBS-Tween 80 (1% wt) at a ratio of 1:1 and mixing.
[0044] According to an embodiment of the present invention, in step a), the molar ratio of the first encapsulating material to the CO molecular prodrug-first carrier is 1:(1-3), for example, 3:5.
[0045] As an example, coating mesoporous hydroxyapatite loaded with carbonyl manganese with chitosan includes the following steps: mixing chitosan and mesoporous hydroxyapatite-carbonyl manganese in a ratio of 3:5 in a Tris-HCl solution.
[0046] According to an embodiment of the present invention, in step b), the molar ratio of the NO molecular prodrug to the second carrier is 1:(1-2), for example, the molar ratio of the mesoporous bioactive glass to arginine is 1:1.
[0047] According to an embodiment of the present invention, loading arginine powder into mesoporous bioactive glass comprises the following steps: adding arginine powder and mesoporous bioactive glass into PBS-Tween 80 (1% wt) at a ratio of 1:1.
[0048] According to an embodiment of the present invention, coating the NO molecular prodrug-second carrier with the second encapsulating material in step b) comprises the following steps: mixing tannic acid and mesoporous bioactive glass-arginine in a ratio of 3:5 in a Tris-HCl solution.
[0049] According to an embodiment of the present invention, in step c), the mass ratio of polyvinyl alcohol, chitosan and deionized water is 10: (0.1-1) 0.5: 90 (80-100).
[0050] According to an embodiment of the present invention, in step c), the mass ratio of the first porous carrier loaded with CO molecular prodrug, the first porous carrier loaded with NO molecular prodrug, hydroxyapatite, bioactive glass, polyvinyl alcohol, and chitosan is 0.00125:0.00025:3:3:3.75:0.25.
[0051] According to an embodiment of the present invention, the mixing temperature in step c) is 60-120 degrees Celsius, and the mixing time is 1-5 hours, for example, the mixing temperature is 90° C., and the mixing time is 2 hours.
[0052] Preferably, a first porous carrier quantitatively loaded with carbonyl manganese and a second porous carrier loaded with arginine are added in proportion to keep the concentrations of carbonyl manganese and arginine at 125 μg / mL and 25 μg / mL;
[0053] According to an embodiment of the present invention, in step (2), the filling density of the cryo-3D printing is 40%-60%.
[0054] According to an embodiment of the present invention, the hydroxyapatite powder is prepared by the following method: calcium nitrate tetrahydrate, diammonium hydrogen phosphate, ammonia water and deionized water are mixed in a molar ratio of 10:6:8:(800-1200), and the hydroxyapatite powder is prepared by a coprecipitation method at 70°C for 2h.
[0055] According to an embodiment of the present invention, the mesoporous bioactive glass is made by the following method: hexadecyltrimethylammonium bromide, triethanolamine, tetraethyl orthosilicate, cyclohexane and triethyl phosphate are mixed in a mass ratio of 12:0.36:12:48:1 to synthesize SPN particles (95% mol SiO2:5% mol P2O5), the SPN particles are mixed with calcium nitrate tetrahydrate in a molar ratio of 1:2, and the mesoporous bioactive glass is prepared by stirring for 12 hours using a template method.
[0056] As an example, step (2) includes the following steps: filling carbonyl manganese powder into mesoporous hydroxyapatite, coating the mesoporous hydroxyapatite loaded with carbonyl manganese with chitosan, and obtaining mesoporous hydroxyapatite + carbon-based manganese / chitosan powder; filling arginine powder into mesoporous bioactive glass, coating the mesoporous bioactive glass loaded with arginine with tannic acid, and obtaining mesoporous bioactive glass + arginine / tannic acid powder; mixing polyvinyl alcohol solution, chitosan solution, mesoporous hydroxyapatite + carbon-based manganese / chitosan powder, mesoporous bioactive glass + arginine / tannic acid powder, hydroxyapatite powder, and bioactive glass powder to prepare printing ink; and printing the ink layer by layer using cryo3D printing technology to obtain a drug-loaded stent.
[0057] In a third aspect, the present invention provides a stent prepared by the above method, wherein the stent comprises a base stent, a drug-loaded stent is attached to the base stent, and the surfaces of the base stent and the drug-loaded stent are coated with nano short fibers.
[0058] According to an embodiment of the present invention, the substrate support, drug-loaded support and nano-short fibers have the definitions as described above.
[0059] Beneficial Effects
[0060] 1) Nitric oxide (NO) and carbon monoxide (CO) are two important endogenous gas signal molecules that play an important role in regulating the phenotypic conversion of macrophages. Nitric oxide (NO) and carbon monoxide (CO) regulate the balance of M1 / M2 phenotype conversion of macrophages through synergistic effects. It has been reported that NO plays an important role in vasodilation, angiogenesis, immune response, wound repair, etc. NO can accelerate wound healing through various mechanisms, such as increasing myofibroblasts, wound contraction, and collagen deposition. At the same time, NO can promote the polarization of macrophages to M1 phenotype, which is used to remove dead cells at the site of injury; CO can inhibit inflammatory response, promote the polarization of macrophages to M2 phenotype, and promote bone tissue repair. Therefore, the function and metabolism of macrophages can be regulated by changing the interaction between NO and CO, thereby affecting the polarization of macrophages. The synergistic effect of NO and CO can promote the transformation of macrophages to a specific polarization state, regulate the M1 / M2 balance of macrophages, and enhance the immune surveillance and immunoregulatory functions of macrophages.
[0061] Arginine (Arg) as a NO molecular prodrug can be converted into L-citrulline in vivo under the stimulation of the damaged bone microenvironment, producing an equimolar amount of NO, polarizing macrophages to the M1 phenotype to clear dead cells at the site of injury, significantly reducing the level of pro-inflammatory cytokines, increasing the level of anti-inflammatory factors, and promoting angiogenesis. NO accelerates the metabolism of intracellular glutathione (GSH) and reduces the clearance of active free radicals that can induce cell apoptosis. NO can react with superoxide ions (O 2·– ) to generate peroxynitrite anion (ONOO – ), a major reactive nitrogen species (RNS), is more effective than most reactive oxygen species (ROS) in inducing apoptosis by peroxidation and nitration of biomolecules. In addition, the guanidine group in arginine can be oxidized by endogenous H2O2, which is rich in the microenvironment of damaged bones, to produce NO, which induces bacterial apoptosis to resist bone infection; arginine can reduce oxidative stress during bone healing by converting to NO, and its antioxidant effect helps protect cells from oxidative damage and promote bone healing. NO can also increase the expression of vascular endothelial growth factor VEGF and promote angiogenesis.
[0062] Manganese carbonyl (MnCO) is an excellent CO molecular prodrug that can rapidly release CO gas and Mn under the stimulation of an inflammatory microenvironment with high reactive oxygen species. 2+ , polarizing macrophages to the M2 phenotype. CO inactivates Toll-like receptor 4 (TLR4) by inhibiting NADPH oxidase activity, downregulating the expression of inflammatory response-related genes, thereby greatly improving the inflammatory response. Endogenous H2O2 rich in the damaged bone microenvironment reacts with MnCO in a Fenton-like reaction, continuously releasing CO and Mn 2+ , up-regulating the M2 phenotype of macrophages and significantly reducing the inflammatory response. 2+ MBGs particles can cooperate with M2 macrophages to secrete VEGF and activate the HIF-1α pathway, inhibiting osteoclast differentiation and further promoting angiogenesis.
[0063] When an inflammatory reaction occurs, the pH value of the body environment will become acidic due to the generation of ROS, changes in cell metabolism, and accumulation of lactic acid caused by insufficient oxygen supply. When the inflammation disappears, the body environment will return to alkaline or neutral. In the present invention, a layer of tannic acid (TA) is coated on the outer layer of the NO release carrier, and the nanocarrier encapsulation layer formed by tannic acid can spontaneously degrade under acidic conditions, thereby achieving drug release under acidic microenvironment pH. The introduction of the cross-linking agent tetraethylenepentamine (TEPA) allows the self-assembled polymer to dissociate into a loose state without degradation under acidic conditions, and when the solution returns to alkaline or neutral, the dissociated polymer can be reassembled into a closed state again by regulating the protonation and deprotonation of TEPA, thereby achieving the stop of drug release and the stop of macrophage transformation to the M1 phenotype when the body environment is restored.
[0064] 2) The present invention uses a preliminary rapid low-temperature freezing and then freeze-drying process during the printing process to quickly change the internal solvent of the ink from liquid to gas, remove ice crystals, and form a porous structure of the material, which is conducive to better cell attachment and angiogenesis. The fiber membrane obtained by electrospinning in this application has a significant ability to control cell behavior, such as cell adhesion and proliferation, which is crucial for the integration of scaffolds and tissues. Compared with dense scaffolds, scaffolds that simulate extracellular matrix (ECM) can better promote the delivery of oxygen and nutrients and the growth of tissues. Electrospinning technology is a widely used method for manufacturing nanofiber structures similar to natural ECM. Electrospinning is combined with 3D printing technology to manufacture BGs short fibers, and hierarchical scaffolds are constructed using the different degradation rates of electrospun nanofibers and 3D printed microfilaments. Ions are released sequentially from the bionic scaffolds for timely vascularization and stable bone formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] Figure 1 This is a physical picture of the composite stent prepared in Example 1;
[0066] Figure 2 The actual picture of the ink printing of different proportions of inorganic phase hydroxyapatite and bioactive glass in Experimental Example 1;
[0067] Figure 3 is the Pr value of the ink with different ratios of inorganic phase hydroxyapatite and bioactive glass in Experimental Example 1;
[0068] Figure 4 The relationship between the ink viscosity and shear rate of different ratios of inorganic phase hydroxyapatite and bioactive glass in Experimental Example 1;
[0069] Figure 5 A comparison of the loss modulus (G") and storage modulus (G') of the scaffolds prepared by the inks of different ratios of inorganic phase hydroxyapatite and bioactive glass in Experimental Example 1;
[0070] Figure 6 The cyclic strain test diagram of the scaffold prepared by the ink of inorganic phase hydroxyapatite and bioactive glass in different proportions in Experimental Example 1;
[0071] Figure 7 This is the effect of different concentrations of sodium alginate cross-linking on the mechanical properties of the scaffold in Experimental Example 2. DETAILED DESCRIPTION
[0072] The following will further describe the ink composition of the present invention, its preparation method and application in combination with specific examples. It should be understood that the following examples are only for illustrative purposes and explanation of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope of protection of the present invention.
[0073] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0074] Example 1
[0075] (1) 0.5062 mol Ca(NO3)2.4H2O and 0.3104 mol (NH4)2HPO4 were dissolved in 500 mL of deionized water, respectively, and then magnetically stirred at room temperature to completely dissolve them, respectively preparing solutions A and B, and then introducing solution B into solution A to obtain solution C and slightly heating it to 20-50°C. Ammonia water was added to solution C, and the pH of solution C was adjusted to 9.5-10 using a pH meter, and then solution C was heated in a 70°C water bath and vigorously stirred for 2 h. After the reaction was completed, the obtained white precipitate was filtered and washed with deionized water 3 times and anhydrous ethanol 3 times. The filtered product was dried at 60°C for 24 h and sintered at 80°C for 2 h to remove impurities, and finally hydroxyapatite powder was obtained.
[0076] (2) Polylactic acid and the hydroxyapatite powder in step (1) were mixed in a mass ratio of 4:6 to obtain printing ink, and cylindrical models of Φ15×5 mm and Φ15×30 mm were constructed using modeling software and slice files were exported using slicing software. The layer thickness was 0.6 mm and the filling density was 50%. Then, an extrusion 3D printer was used to print the "ink" layer by layer under the control of the gcode code to obtain a PLA-HA scaffold.
[0077] (3) 2.14 g of diammonium hydrogen phosphate was added to 300 mL of deionized water containing 2 g of CTAB (hexadecyltrimethylammonium bromide), the pH was adjusted to 10, and 100 mL of an aqueous solution containing 6.3747 g of calcium nitrate tetrahydrate was slowly added, the pH was adjusted to 10 again, and the mixture was reacted at 90° C. for 24 h. After the reaction was completed, the mixture was centrifuged at 5000 rpm, washed three times with ethanol and water in turn, dried, and sintered at 500° C. for 2 h to remove CTAB, thereby finally obtaining mesoporous hydroxyapatite (MHA).
[0078] (4) 0.5 g MHA and 0.5 g MnCO powder were ultrasonicated in 100 ml PBS-Tween 80 (1 wt%) for 10 min to remove bubbles in the mesopores, stirred at 37 °C in the dark for 12 h, centrifuged at 5000 rpm, and the precipitate was freeze-dried to obtain MHA / MnCO powder.
[0079] (5) 2 g CS (chitosan) powder was dissolved in 100 ml deionized water and stirred until dissolved. 1 ml (1%) glacial acetic acid was added dropwise and the mixture was sealed and stirred for 1 h to obtain CS solution (1%). 1 g MHA / MnCO was dispersed in 100 ml deionized water and stirred for 20 min. The CS solution was slowly added to MHA / MnCO (keeping stirring). The mixture was sealed and stirred for 12 h, then centrifuged, washed and freeze-dried to obtain MHA-MnCO / CS powder.
[0080] (6) 12 g CTAB and 0.36 ml TEA (triethanolamine) were dissolved in 108 ml deionized water to obtain water-CTAB-TEA, which was stirred at 60° C. for 1 h. 12 ml TEOS and 48 ml cyclohexane were mixed evenly and then slowly added to the water-CTAB-TEA. After stirring at 60° C. for 3 h, 0.921 ml TEP (triethyl phosphate) was added and the mixture was reacted at 60° C. for 9 h. After the reaction, the mixture was centrifuged at 5000 rpm, washed three times with ethanol and water in sequence, and freeze-dried to obtain SPN particles (95% mol SiO2: 5% mol P2O5).
[0081] (7) 0.704 g of calcium nitrate tetrahydrate was dissolved in 40 ml of ethanol, 1 g of SPN particles was added, and the mixture was stirred for 12 h until the ethanol evaporated. The mixture was sintered at 600 °C for 5 h to remove the template, and the mixture was sieved to obtain mesoporous bioactive glass (MBG).
[0082] (8) 0.5 g MBG and 0.5 g Arg powder were sonicated in 100 ml PBS-Tween 80 (1 wt%) for 10 min to remove bubbles in the mesopores, stirred at 37°C for 12 h, centrifuged at 5000 rpm, and the precipitate was freeze-dried to obtain MBG-Arg powder.
[0083] (9) 2 g of MBG-Arg powder was ultrasonically dispersed in a Tris-HCl buffer solution (100 ml, pH 8.5), and TA (50 mg) and TEPA (tetraethylenepentamine) (20 ml) were added. After stirring for 8 h in the dark, the mixture was centrifuged, washed, and freeze-dried to obtain MBG-Arg / TA powder.
[0084] (10) 3 g of HA, 0.0025 g of MHA-MnCO / CS powder, 3 g of BG, and 0.0005 g of MBG-Arg / TA powder were weighed and dissolved in 26 mL of an aqueous solution containing 3.75 g of polyvinyl alcohol and 0.25 g of chitosan, and stirred to obtain a freeze-printing ink.
[0085] (11) Use modeling software to construct cylindrical models of Φ15×5mm and Φ15×30mm and use slicing software to export slicing files, with a layer thickness of 0.6mm and a filling density of 50%. Then, use an extrusion 3D printer to print the "ink" in step (10) layer by layer under the control of the gcode code to obtain a scaffold. After printing, soak the scaffold in sodium alginate solutions of different concentrations (10, 20, 30, 40g / L) for 2h to obtain a polyvinyl alcohol-hydroxyapatite / chitosan-bioactive glass / tannic acid scaffold, freeze-dry it in a freeze dryer for 48h, and name the scaffold PVA-MHA / CS-MBG / TA (hereinafter referred to as drug-loaded scaffold).
[0086] (12) The PLA-HA substrate scaffold is composited with an organic solvent, dichloromethane, and the surface is evenly covered with a layer of dichloromethane. The PLA-HA substrate scaffold is taken out and placed on the drug-loaded scaffold to ensure that the two are in contact and bonded together. The PLA substrate scaffold is dried in a ventilated environment. As the solvent dichloromethane evaporates, the PLA will re-solidify to form a solid bonding layer, so that the substrate scaffold and the drug-loaded scaffold are firmly composited together to obtain a first composite scaffold.
[0087] (13) MBG-Arg / TA powder was added into anhydrous ethanol (the arginine content in the suspension was kept at 25 μg / ml) and stirred evenly to obtain a stable bioactive glass ethanol suspension to prepare the electrospinning solution.
[0088] (14) MBG-Arg / TA fiber membrane was spun using an electrospinning machine at a voltage of 17 kV, a flow rate of 1 mL / h, and a working distance of 20 cm. The membrane was sintered at 800 °C for 1 h, dispersed in tert-butanol, and homogenized in a homogenizer for 5 min (104 rpm) to obtain a nano-short fiber dispersion solution. The first composite scaffold was immersed in the nano-short fiber dispersion solution and freeze-dried at -20 °C to obtain a second composite scaffold. The scaffold obtained by freeze-drying was named polylactic acid-polyvinyl alcohol-hydroxyapatite / carbonyl manganese-bioactive glass / arginine scaffold.
[0089] Comparative Example 1
[0090] In order to verify the effect of the introduction of carbonyl manganese and arginine on the printability of the scaffold, this comparative example is the same as Example 1 except that steps (4)-(5), (8)-(9) are removed and MHA-MnCO / CS powder is replaced by hydroxyapatite powder and MBG-Arg / CS is replaced by bioactive glass powder in step (10). That is, carbonyl manganese and arginine are not added in this comparative example 1.
[0091] A PVA-MHA-MBG ink without carbonyl manganese and arginine was prepared. 3.0025 g of the prepared hydroxyapatite powder and 3.0005 g of the bioactive glass powder were dispersed in an aqueous solution with a solid content of 3.75 g of polyvinyl alcohol and a solid content of 0.25 g of chitosan, and stirred evenly with a glass rod to form a composite ink, named PVA-MHA-MBG.
[0092] The cylindrical models of Φ15×5mm and Φ15×30mm were constructed using modeling software and sliced files were exported using slicers, with a layer thickness of 0.6mm and a filling density of 50%. Then, an extrusion 3D printer was used to print the "ink" layer by layer under the control of the gcode code.
[0093] Experimental Example 1
[0094] In this study, we aimed to explore the effect of bioink formulation on scaffold printability and to optimize the ratio of inks with the best printability. The evaluation of bioink printability was performed by a semi-quantitative method based on rheological measurements and image analysis.
[0095] The printability of the scaffolds prepared in Example 1 and Comparative Example 1 is measured based on the fidelity (Pr):
[0096] Pr=L 2 / 16A
[0097] Wherein, L represents the perimeter of the square grid surrounded by the stents, and A represents the enclosed area. Each group of stents was photographed (n=5), and the stents were observed using an optical microscope to measure the perimeter and area of the grid.
[0098] The experimental results show that the printing effects of the scaffolds with different ratios in Example 1 (when other conditions remain unchanged, the ratio of inorganic phase hydroxyapatite to bioactive glass in the scaffold printing slurry is changed to 1:1-10%, 1:1-15%, 1:2-10%, 1:2-15%, 2:1-10%, 2:1-15%, where the percentage is the concentration of organic phase polyvinyl alcohol and chitosan) are different, and their Pr values further verify this result, where the closer the Pr value is to 1, the better the printability of the scaffold, see Figure 2 and Figure 3 As shown, when the ratio of inorganic phase hydroxyapatite to bioactive glass in the scaffold printing slurry is 1:1, and the concentration of organic phase polyvinyl alcohol and chitosan is 15%, the Pr value is closest to 1. At this time, the grid formed by printing is obvious and there is no breakage.
[0099] The rheological properties of the ink are also a key factor in evaluating printability. This experimental example further explored the relationship between the viscosity and shear rate of the bio-ink, revealing a pseudoplastic behavior characterized by shear thinning, see Figure 4 and Figure 5 As shown, further analysis of the ink modulus shows that within the entire strain range, the loss modulus (G") of the scaffold in Example 1 (2:1-15% and 1:2-10%) is still higher than the storage modulus (G'), revealing its viscosity is higher than its elasticity, so it is easy to collapse after extrusion, which is consistent with the Pr value structure. In contrast, at low strains, the G' of the 2:1-10%, 1:1-10%, 1:2-15% and 1:1-15% scaffolds in Example 1 exceeds G", indicating that the elasticity of the bio-ink after extrusion is dominant, which is beneficial for the ink to maintain a stable structure without collapse during post-extrusion.
[0100] The rapid self-healing ability of the ink in the examples was then evaluated, see Figure 6 As shown, cyclic strain demonstrated that the four optimal ratios of bio-inks in Example 1 (1:1-10%, 1:1-10%, 1:2-15% and 1:1-15%) showed alternating transitions of G' and G", which means a reversible transition from a gel to a fluid state, however, the 2:1-15% and 1:2-10% scaffolds in Example 1 lacked the ability to recover to the gel state at low strain and therefore lacked printability.
[0101] Experimental Example 2
[0102] Mechanical properties are an important factor in reflecting the biomechanical hierarchy of scaffolds. In this study, our purpose was to explore the effect of cross-linking with different concentrations of sodium alginate on the mechanical properties of scaffolds, and to optimize the concentration of sodium alginate cross-linked scaffolds that achieve the best mechanical properties after cross-linking, and to evaluate the mechanical properties of the scaffolds based on stress-strain tests.
[0103] The experimental results can be found in Figure 7 As shown, the mechanical properties of the scaffolds with different sodium alginate cross-linking ratios (0%, 10%, 20%, 30%) in Example 1 are different, and the scaffold obtained after cross-linking with a sodium alginate concentration of 20 g / L has the best mechanical properties.
[0104] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. An ink composition having a synergistic signal molecule, characterized in that: The ink composition includes a first porous carrier loaded with a CO molecular prodrug and a second porous carrier loaded with a NO molecular prodrug, wherein the surface of the first porous carrier is coated with a first encapsulating layer, the first encapsulating layer is used to block the CO molecular prodrug in the pores of the first porous carrier, and the first encapsulating layer can self-degrade and release CO molecules under high oxygen activity conditions; the surface of the second porous carrier is coated with a second encapsulating layer, the second encapsulating layer is used to block the NO molecular prodrug in the pores of the second porous carrier, and the second encapsulating layer can self-degrade and release NO molecules under acidic conditions.
2. The ink composition having cooperative signal molecules according to claim 1, characterized in that: The ink composition also includes hydroxyapatite, bioactive glass, polylactic acid, polyvinyl alcohol and chitosan. Preferably, the ink composition further comprises a solvent, and the solvent comprises one or more of deionized water, ethanol, propanol, dichloromethane, dimethyl sulfoxide, dimethylformamide, and glycerol. Preferably, the CO molecular prodrug is selected from materials that can release CO molecules in body fluids, preferably selected from one or more of metal carbonyl compounds such as carbonyl manganese, carbonyl imidazoles, nitroxyl compounds, heme derivatives, and CO metal complexes. Preferably, the NO molecular prodrug is selected from materials that can release NO molecules in body fluids, preferably one or more selected from arginine, citrulline, dimethylarginine, nitro drugs, organic nitrates, nitrosothiol compounds, metal-nitrosyl complexes, and diazeniumdiolate salts.
3. The ink composition having cooperative signal molecules according to claim 1 or 2, characterized in that: The first porous carrier is selected from biocompatible mesoporous materials, preferably selected from one or more of mesoporous hydroxyapatite, mesoporous bioactive glass, mesoporous silicon, mesoporous carbon, metal organic framework, and metal oxide mesoporous materials. According to an embodiment of the present invention, the second porous carrier is selected from biocompatible mesoporous materials, preferably selected from one or more of mesoporous bioactive glass, mesoporous hydroxyapatite, mesoporous silicon, mesoporous carbon, metal organic framework, and metal oxide mesoporous materials. Preferably, the first encapsulating layer and the second encapsulating layer are independently selected from one or more of chitosan, polylactic acid, polyvinyl alcohol, tannic acid, sodium alginate and gelatin. Preferably, the mass ratio of the first porous carrier loaded with CO molecular prodrug to the second porous carrier loaded with NO molecular prodrug is 1 (1-5):1 (1-5).
4. A method for freezing 3D hierarchical printing of a stent using the ink composition according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing polylactic acid and hydroxyapatite powder to print a base support; (2) mixing the first porous carrier loaded with CO molecular prodrug, hydroxyapatite, bioactive glass powder, polyvinyl alcohol and chitosan solution for cryo-3D printing to obtain a drug-loaded stent; (3) Fixing the base support and the drug-loaded support to obtain a first composite support. Preferably, step (3) comprises the following steps: immersing the base support in an organic solvent so that the base support is completely covered with the organic solvent, dissolving the polylactic acid on the surface of the base support, contacting and bonding the base support with the drug-loaded support, and drying to obtain a first composite support.
5. The preparation method according to claim 4, characterized in that: After step (2) and before step (3), the method further includes the following steps: immersing the drug-loaded stent in a sodium alginate solution and drying the stent. Preferably, the concentration of sodium alginate is 5 to 60 g / L, the drying is freeze drying, the freeze drying temperature is -30°C to -10°C, and the time is 15 to 35 hours.
6. The preparation method according to claim 4, characterized in that: The method further comprises step (4) after step (3): dissolving the second porous carrier loaded with NO molecular prodrug in a solvent and performing electrospinning to obtain a fiber membrane, dispersing the fiber membrane in a dispersion liquid and homogenizing at high speed to obtain a nano-short fiber dispersion solution, immersing the first composite scaffold in the nano-short fiber dispersion solution, and then drying to obtain a second composite scaffold. Preferably, the drying is freeze-drying, and the concentration of arginine in the suspension of step (4) is 10 to 50 μg / mL.
7. The preparation method according to any one of claims 4 to 6, characterized in that: The step (2) comprises the following steps: a) loading the CO molecular prodrug into the first carrier, and coating the CO molecular prodrug-first carrier with a first encapsulating material to form a first porous carrier loaded with the CO molecular prodrug; b) loading the NO molecular prodrug into the second carrier, and coating the NO molecular prodrug-second carrier with a second encapsulating material to form a second porous carrier loaded with the NO molecular prodrug; c) mixing a polyvinyl alcohol solution, a chitosan solution, a first porous carrier loaded with a CO molecular prodrug, a second porous carrier loaded with a NO molecular prodrug, hydroxyapatite powder, and a bioactive glass powder to prepare a printing ink, and printing the ink layer by layer using a cryo-3D printing technique to obtain a drug-loaded stent.
8. The preparation method according to claim 7, characterized in that: In step a), the molar ratio of the CO molecular prodrug to the first carrier is 1:(1-2). Preferably, in step a), the molar ratio of the first encapsulating material to the CO molecular prodrug-first carrier is 1:(1-3). Preferably, in step b), the molar ratio of the NO molecular prodrug to the second carrier is 1:(1-2). Preferably, in step c), the mass ratio of polyvinyl alcohol, chitosan and deionized water is 10:(0.1-1)0.5:90(80-100).
9. The preparation method according to any one of claims 4 to 6, characterized in that: In step (2), the filling density of the frozen 3D printing is 40%-60%.
10. A stent prepared by the method according to any one of claims 4 to 9, characterized in that: The support comprises a base support, a drug-loaded support is attached to the base support, and the surfaces of the base support and the drug-loaded support are coated with short nanofibers.
Citation Information
Patent Citations
Preparation method of phosphorene-functional-modified 3D-print polylactic acid bionic nanofiber support
CN113368303A
Connecting bracket of wire cable for air dome
KR102797052B1
Nitric oxide-releasing 3d-printing compositions and uses thereof
US20210301135A1
Nitric oxide releasing nail coating compositions, nitric oxide releasing nail coatings, and methods of using the same
WO2016010988A1